Detection of Human Intestinal Catalase-Negative, Gram-Positive Cocci by rRNA-Targeted Reverse Transcription-PCR - Kubota, Hiroyuki (American Society for Microbiology (ASM), 2010)
An analytical system based on rRNA-targeted reverse transcription-quantitative PCR (RT-qPCR) for enumeration of catalase-negative, Gram-positive cocci was established. Subgroup- or species-specific primer sets targeting 16S or 23S rRNA from Enterococcus, Streptococcus, and Lactococcus were newly developed. The RT-qPCR method using these primers together with the previously reported primer sets specific for the Enterococcus genus, the Streptococcus genus, and several Streptococcus species was found to be able to quantify the target populations with detection limits of 10(3) to 10(4) cells per gram feces, which was more than 100 times as sensitive as the qPCR method (10(6) to 10(8) cells per gram feces). The RT-qPCR analysis of fecal samples from 24 healthy adult volunteers using the genus-specific primer sets revealed that Enterococcus and Streptococcus were present as intestinal commensals at population levels of log(10) 6.2 ± 1.4 and 7.5 ± 0.9 per gram feces (mean ± standard deviation [SD]), respectively. Detailed investigation using species- or subgroup-specific primer sets revealed that the volunteers harbored unique Enterococcus species, including the E. avium subgroup, the E. faecium subgroup, E. faecalis, the E. casseliflavus subgroup, and E. caccae, while the dominant human intestinal Streptococcus species was found to be S. salivarius. Various Lactococcus species, such as L. lactis subsp. lactis or L. lactis subsp. cremoris, L. garvieae, L. piscium, and L. plantarum, were also detected but at a lower population level (log(10) 4.6 ± 1.2 per gram feces) and prevalence (33%). These results suggest that the RT-qPCR method enables the accurate and sensitive enumeration of human intestinal subdominant but still important populations, such as Gram-positive cocci.